Investigating the game-related statistics and tactical profile in NCAA division I men’s basketball games - Conte, Daniele; Tessitore, Antonio; Gjullin, Aaron; Mackinnon, Dominik; Lupo, Corrado; Favero, Terence (Biology of Sport, 2018)
The aim of this study was to analyze the game-related statistics and tactical profile in winning and losing teams in NCAA division I men’s basketball games. Twenty NCAA division I men’s basketball close (score difference: 1-9 points) games were analyzed during the 2013/14 season. For each game, the gamerelated statistics were collected from the official teams’ box scores. Number of ball possessions, offensive and defensive ratings and the Four Factors (effective field goal percentage; offensive rebounding percentage, recovered balls per ball possession, free throw rate) were also calculated. The tactical parameters evaluated were: ball reversal, dribble in key area, post entry, on-ball screen, off-ball screen, and hand off. Differences between winning and losing teams were calculated using a magnitude-based approach. Winning teams showed a likely higher percentage of 3-point goals made, number of defensive rebounds and steals and a very likely higher number of free throws made and free throws attempted. Furthermore, winning teams showed a likely higher team offensive rating and effective field goal percentage and a very likely higher free throw rate compared to losing teams. Finally, the results revealed a likely higher number of ball reversals and post entries in winning teams compared to losing teams. This study highlighted the game-related statistics and the tactical actions differentiating between winning and losing teams in NCAA Division I men’s basketball close games. Coaches should use these results to optimize their training sessions, focusing on those variables that might increase the possibility to win close games.